2016
DOI: 10.1002/path.4745
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo effector TAZ (WWTR1) transforms myoblasts and TAZ abundance is associated with reduced survival in embryonal rhabdomyosarcoma

Abstract: The Hippo effector YAP has recently been identified as a potent driver of embryonal rhabdomyosarcoma (ERMS). Most reports suggest that the YAP paralogue TAZ (gene symbol WWTR1) functions as YAP but, in skeletal muscle, TAZ has been reported to promote myogenic differentiation, whereas YAP inhibits it. Here, we investigated whether TAZ is also a rhabdomyosarcoma oncogene or whether TAZ acts as a YAP antagonist. Immunostaining of rhabdomyosarcoma tissue microarrays revealed that TAZ is significantly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 61 publications
3
40
1
Order By: Relevance
“…In pathologic conditions, phosphorylation of TAZ leads to its cytoplasmic retention and delays myogenic differentiation. 23 Similarly, YAP is retained in the nucleus, where it promotes satellite cells proliferation, and prevents their differentiation. Rhabdomyosarcomas are tumors of skeletal muscle origin that exhibit overexpression of the myogenic regulatory proteins, MYOD1 and myogenin.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
See 4 more Smart Citations
“…In pathologic conditions, phosphorylation of TAZ leads to its cytoplasmic retention and delays myogenic differentiation. 23 Similarly, YAP is retained in the nucleus, where it promotes satellite cells proliferation, and prevents their differentiation. Rhabdomyosarcomas are tumors of skeletal muscle origin that exhibit overexpression of the myogenic regulatory proteins, MYOD1 and myogenin.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…26 Additional data have also suggested that TAZ may play a role, albeit less prominent than that of YAP, in the pathogenesis of aRMS. 23 YAP overexpression is also implicated as a key factor in the development of embryonal rhabdomyosarcoma (eRMS). A recent study using multiple genetically engineered mice has demonstrated that YAP protein overexpression transforms activated satellite cells leading to the development of embryonal rhabdomyosarcoma-like tumors.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
See 3 more Smart Citations